TRENDS TOWARDS POLITICAL COMMUNICATION STRATEGY ON SOCIAL MEDIA: A BIBLIOMETRICS ANALYSIS - Hanifah, Annisa Atha; Mani, La; Busthomi, Zidane Ahmad; Sunrise, Giovanni; Kristanto, Matthew Abrham; Prawira, Indra (JWP (Jurnal Wacana Politik), 2026)
Social media has become the centre of digital political communication, enabling politicians to convey messages, form narratives, and mobilise public support directly and interactively. Social media platforms such as Twitter, Instagram, and TikTok serve not only as campaign tools but also as deliberative spaces where political discourse is formed and debated. This study uses a bibliometric approach to analyse global trends in research on political communication on social media during the period 2020-2024. Data were collected in October 2025 from the Scopus database, comprising 608 documents from 253 publication sources and author affiliations in 24 countries. The search was conducted using queries with keywords “political communication”, “social media”, and “public response”. The analysis was conducted using VOS viewer and RStudio (Biblioshiny) to map author collaboration networks, keyword interrelationships, thematic distribution, and identification of most productive journals and institutions. The results show four main clusters in global literature: digital campaign strategies by political elites, issue mobilisation and public engagement, algorithmic influence on message framing and issue visibility, and ethical governance and the challenges of disinformation. These findings enrich the theory of digital political communication and provide new directions for research on the relationship between technology, democracy, and political participation in virtual public spaces.